EVANESCENCE’S FALLEN SOUND DEVICES AND ITS CONTRIBUTION TO LANGUAGE TEACHING OF POETRY - Aliyatis Sya’ni (ETERNAL (English Teaching Journal), 2014)
Poetry is a feeling expression that uses chosen words, that is not predicted and has powerful meaning. Kennedy and Gioia explain that poetry is another way to say or another term is poem. A poem usually will make some sense and give some pleasure, but it may not yield everything at once. Many kinds of poetry, one of them is song lyric. A good song lyric has good sound devices. Sound device is one of the characteristics of poetry. The aims of the final project are: (1) to find out how Fallen single lyrics contribute to language teaching of poetry, (2) to find out sound devices are used in Fallen lyrics. This final project applied descriptive qualitative method. The data in this final project is collected by downloading from internet and also gathering the other data and theories from some related books from library. The data is analyzed by five steps. First, the songs were listened carefully. Second, reading the song lyrics. Third, the song lyrics were classified in sound devices. Fourth, the song lyrics were analyzed with alliteration, assonance, consonance and rhyme. And the last, reporting the result. The result of this final project can be briefly in clear description as follow. They are eleven songs in the Fallen album. The researcher found out four kinds of sound devices in the song lyrics. They are alliteration, assonance, consonance and rhyme. Based on the song lyrics of Fallen album that analyzed the final project. They are 106 assonances, 63 consonances, 61 alliterations and 24 rhymes (14 internal rhymes, 6 perfect rhymes, 3 end rhymes and 1 imperfect rhymes). Fallen single lyrics can contribute to language teaching poetry. Lyrics in the fallen album are easy to be analyzed by students. Besides on those sound devices of Fallen album can make students enjoy in learn poetry. Students can get knowledge more about correlation between poetry and song, they can find out elements of poetry through song and be more creative in learning English.